Deletions in the DNA-binding domain of the TP53 gene in v-src-transformed chicken cells - Trtková, Katerina; Plachý, Jirí (In vitro cellular & developmental biology. Animal, 2004)
We have examined the chicken TP53 tumor suppressor gene in v-src-transformed chicken tumor cells by reverse transcriptase-polymerase chain reaction and deoxyribonucleic acid (DNA) sequencing. Initially, we have detected frequent deletions of variable length in both DNA-binding and oligomerization domains of the TP53 in late as well as early in vitro passages of the chicken tumor cell line PR9692. This tumor cell line shows an immortal phenotype and acquires a metastatic potential that is unique in our experimental model of v-src-induced tumors in congenic chickens. Deletions in TP53 were also detected in an early passage of parallel in vivo subculture of the original v-src-induced tumor. In this case, tumor cells underwent replicative senescence later in tissue culture. Our results suggest that extensive deletions are efficient mechanisms of TP53 inactivation, occurring as early events during the immortalization of v-src-transformed chicken cells. Tumor cells with altered TP53 might, however, still be susceptible to growth control mechanisms, leading to withdrawal from the mitotic cycle in the early stage of the tumor lifeline.
Keywords: kur domácí; Cell Line, Transformed; nádorová transformace buněk; transformované buněčné linie; sekvence nukleotidů; geny src; Neoplasm Metastasis; Cell Line, Tumor; Genes, src; Chickens; umlčování genů; Cell Transformation, Neoplastic; molekulární sekvence - údaje; Genes, p53; sekvenční seřazení; geny p53; Animals; zvířata; Molecular Sequence Data; Base Sequence; Gene Silencing; nádorové buněčné linie; metastázy nádorů; Sequence Alignment